REAKSI PASAR TERHADAP PENGUMUMAN INVESTASI - Borolla, Johanis Darwin (PRESTASI, 2010)
This research is testing the capital market reaction towards investment announcement which is published by company in Bloomberg News Service. The model that used to test the market reaction around the publishing date of investment information is market adjusted model. This model is appropriate to be use in abnormal return calculation for capital market in developing country, because generally the securities are not traded in certain times (in-synchronized trading) which is concluded in biased Beta calculation. The research resulted that in 21 days examination (10 days before and after, and at the day of the announcement) the market reaction is vary around the day. This is proven by the abnormal return occurred. T-test results are 0.040 significant positive at the h+5 day and 0.063 significant positive at the h+9 day, also 0.05 significant negative at h+7 day.Keyword : investment announcement, market reaction